From Learning to Earning: Investigating the Role of Social Media in Education and Employment for English Education Graduates - Hasanah, Uswatun (Loquen, 2025)
This study explores social media's role in education and employment for the fresh graduates of English Education Department (TBI) of Universitas Islam Negeri (UIN) Banten. The massive advancement of social media has shifted some people’s ways of life, including the way individuals acquire knowledge and occupation. It becomes a pivotal tool in broadening access to information, educational resources, and career opportunities. A mix-method was employed in this study by conducting interviews and surveys. 14 participants graduated from the English Education Department of UIN Banten were involved in the data collection on how the use of social media to foster learning, builds professional networks, and enhance relevant skills in labor markets. The main focus of the study is to identify how online platforms such as Instagram, YouTube, TikTok, and other platforms are utilized by the graduates to access teaching materials, and information, and broaden their professional network in language and education. The finding shows that social media substantially improves graduates' ability to find relevant jobs, build portfolios, and be well-informed about the latest developments in English education. However, the study also highlights challenges encountered by social media users to advance their digital literacy to optimize social media features as a supporting tool for education and professional growth.